Модель інтегрального статистичного оцінювання інвестиційної привабливості регіонів України - Степуріна, Світлана Олександрівна; Дериховська, В. І. (My University, 2019)
У статті розглянуто підхід до визначення інвестиційної привабливості регіонів України з позицій теорії складних систем. Оцінка рівня інвестиційної привабливості регіону є інтегральною оцінкою її складників (підсистем), які, своєю чергою, є інтегральними показниками за групами вхідних показників. Установлено, що з позицій статистичної оцінки інвестиційна привабливість будьякого регіону України відображає узагальнений рівень задоволення ринкових, фінансових, виробничих, організаційних та інших вимог або інтересів окремого інвестора щодо певної території, характеризується чинниками регіонального розвитку та може визначатися (оцінюватися) відповідними значеннями факторних та інтегральних оцінок. Також потенційним інвесторам щодо вирішення завдань, пов’язаних із прогнозуванням оптимальних обсягів та вибором адекватних напрямів інвестицій, формуванням оптимальних інвестиційних рішень (множини варіантів вкладень), активізацією інвестиційних процесів та вдосконаленням управління ними на регіональному рівні, доцільно використовувати обґрунтовані оцінки інвестиційної привабливості регіонів України.

The article considers approach to the determination of the investment attractiveness of the regions of Ukraine from the standpoint of the theory of complex systems, assessment of the level of investment attractiveness of the region is an integral assessment of its components (subsystems), which, in turn, are integral indicators by the groups of input indicators. It is established that from the viewpoint of statistical evaluation, investment attractiveness of any region of Ukraine reflects a generalized level of satisfaction of market, financial, production, organizational, and other needs or interests of a certain investor in relation to a certain territory, is characterized by factors of regional development, and can be determined (evaluated) by corresponding values of factor and integral estimates. Also, it is expedient to use reasonable estimates of investment attractiveness of Ukraine’s regions for potential investors in solving problems related to forecasting optimal volumes and choosing relevant investment directions, forming optimal investment decisions (a plurality of investment variants), activating investment processes, and improving their management at the regional level. The study analyses the use of rating evaluation of investment attractiveness of regions, the process of evaluation consists of five consecutive stages. The rating evaluation is based on indicators of general economic development, economic and geographical development of industrial infrastructure, indicators of socio-demographic situation, indicators of development of market relations and commercial infrastructure. Then, on the basis of the results obtained, generalized estimates of investment risk are calculated and the overall rating of Ukrainian regions according to the integral indicator of investment attractiveness is built. In accordance with the obtained integral estimate, groups of Ukrainian regions by investment attractiveness are distinguished, namely: a group of investment-attractive regions, a group of regions with an average level of investment attractiveness, and regions that, according to the calculations, are considered to be investment-unattractive.
Model of integral statistical evaluation of investment attractiveness of regions in Ukraine
Keywords: індикативний простір; інтегральний показник; регіон; рейтингова оцінка; статистична оцінка; indicative space; integral indicator; region; rating evaluation; statistical evaluation